Cognitive disorders in a patient with an arachnoid cyst of the sylvian fissure and improvement after surgical treatment: Case description. Issue 2 (3rd April 2019) - Kwiatkowska, Karolina; Hałabuda, Agata; Rybus, Justyna; Kwiatkowski, Stanisław
ABSTRACT: Arachnoid cysts cause a wide spectrum of clinical symptoms. Often it is difficult to clearly establish the relation between the presence of an arachnoid cyst and problems reported by the patient, which may, although not necessarily, be due to chronically elevated intracranial pressure. In recent years, increasing attention is paid to cognitive disorders accompanying arachnoid cysts, such as memory disorders, attention disorders, or language function disorders. This article presents a case of an 11-year-old patient, treated at the University Children's Hospital in Cracow for an arachnoid cyst, located in the left middle cranial fossa. This analysis is focused on the description of cognitive and intellectual deficits of the child, as well as the discussion on their connection with the arachnoid cyst. Prior to the neurosurgical procedure, the boy presented significant deficits in cognitive functions, especially mnestic and attention functions and, also, a quite low level of intellectual functioning. Neuropsychological examination performed after the procedure indicated a significant improvement of cognitive functioning for all the functions, as well as a higher level of intellectual functioning. This analysis attempts to answer whether and to what extent the child still suffers from cognitive deficits from the organic lesions.